A revision of Zaeucoila Ashmead (Hymenoptera, Figitidae), parasitoids of Agromyzidae (Diptera): new species, identity, distribution, and hosts - Buffington, Matthew L. (2017)
Fil: Buffington, Matthew L.. National Museum of Natural History. Smithsonian Institution. Systematic Entomology Laboratory; USA